2019
DOI: 10.21426/b634043868
|View full text |Cite
|
Sign up to set email alerts
|

On the non-malacostracan crustaceans (Crustacea: Branchiopoda, Copepoda, Ostracoda) from the inland waters of Fthiotida (Greece)

Abstract: On the non-malacostracan crustaceans (Crustacea: Branchiopoda, Copepoda, Ostracoda) from the inland waters of Fthiotida (Greece) Permalink https://escholarship.org/uc/item/8rg409vd Journal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In fact, except for E. serrulatus, T. prasinus (Fischer, 1866), M. viridis, C. divergens, and D. lubbocki, all the other observed copepod species were to date known in Sicily from few sites each, and their status and distribution on the island are currently unknown. Among the Cyclopoida, the finding of Cyclops ankyrae, a rare cyclopid species currently known to occur in temporary water bodies in Sicily [17], peninsular Italy [58,71,72], the southern Balkan peninsula [47], Turkey [55], and Iran [52] is particularly noteworthy; however, it is probable that the populations of C. furcifer Claus, 1857, a mostly North European species reported for Sicilian temporary ponds by Margaritora et al [12], are in fact to be ascribed to C. ankyrae so that the regional distribution of the species could be underestimated. As already stressed for Cyclops abyssorum, the copepod populations belonging to the genus Cyclops in Sicily need a careful revision to ascertain their actual identity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, except for E. serrulatus, T. prasinus (Fischer, 1866), M. viridis, C. divergens, and D. lubbocki, all the other observed copepod species were to date known in Sicily from few sites each, and their status and distribution on the island are currently unknown. Among the Cyclopoida, the finding of Cyclops ankyrae, a rare cyclopid species currently known to occur in temporary water bodies in Sicily [17], peninsular Italy [58,71,72], the southern Balkan peninsula [47], Turkey [55], and Iran [52] is particularly noteworthy; however, it is probable that the populations of C. furcifer Claus, 1857, a mostly North European species reported for Sicilian temporary ponds by Margaritora et al [12], are in fact to be ascribed to C. ankyrae so that the regional distribution of the species could be underestimated. As already stressed for Cyclops abyssorum, the copepod populations belonging to the genus Cyclops in Sicily need a careful revision to ascertain their actual identity.…”
Section: Discussionmentioning
confidence: 99%
“…The coordinates of the sampled water bodies were registered with GPS along with information about their hydroperiods and the possible occurrence of vertebrate predators (i.e., fish or Xenopus laevis tadpoles). In each site and on each sampling date, electric conductivity and water temperature were recorded with a Hanna Instrument HI9835 multiprobe; moreover, an estimate of the abundance of macrophytes and of water turbidity was assessed by using three arbitrary qualitative classes (see Marrone et al [47]).…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Despite its recent, man-made origin, the pond studied has developed a biocoenosis typical of mature temporary ponds (Fig. 2 We used a fragment of the 12S rDNA since this marker has been studied in detail in Andalusian populations (Korn et al 2010), so that a rich comparative dataset is available; 12S rDNA has often been used for the identification of Triops species based on single marker sequences (e.g., Tziortzis et al 2014;Marrone et al 2019). Used primers, PCR mix, and thermal cycles followed Korn et al (2006Korn et al ( , 2010, but PCR products were sent to Macrogen Europe for sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Cases with complex taxonomy were also recorded. Stephanides [6] recorded in Corfu "Diaptomus serbicus = Diaptomus mirus" and Marrone et al [19] recorded Diaptomus cf. serbicus in Fthiotis.…”
Section: Copepodamentioning
confidence: 99%
“…In the mid-1900s, when zooplankton fauna of Greece was still poorly known, Stephanides [6][7][8][9] extensively studied the crustacean fauna of the island Corfu, while Pesce later focused on subterranean copepod fauna from both the islands and the Greek mainland in many publications from 1979 to 1986 [10][11][12][13][14][15][16][17]. More recently, Marrone et al reported 46 taxa from the island of Crete [18] and 20 taxa from the Fthiotis area [19]. These studies demonstrate that biodiversity patterns can actually reflect the areas where taxonomists live and work, or go on holiday or conduct fieldwork [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%